The Relationship Between White Ocean Strategy, Customer Value, and Customer Engagement - Hartini, Sri; Kurniawati, Masmira; Sulistiawan, Jovi; Ihwanudin, Muhammad (Organizations and Markets in Emerging Economies, 2022)
White Ocean Strategy (WOS) has a positive impact on the company. However, many companies have not implemented this strategy. There is a research gap between customer value and customer engagement (CE). This research explains that customer value is an antecedent of CE. However, some studies discuss that customer value is a consequence of CE. This study aims to explain the relationship of WOS, customer value, and CE. This research is quantitative explanatory research and used accidental sampling to obtain the samples. The survey was conducted online with Google Forms distributed on social media and obtained 220 respondents who are users of the Surabaya bus services. The hypotheses were tested using the SEM-PLS. Seven hypotheses were accepted, while other two were rejected. It was found that WOS increases CE, customer green value, functional value, and emotional value. Nevertheless, it does not significantly affect customer social value. The customers’ green, functional, and emotional values impact CE, while social customer values do not affect CE. The contribution of this study is to clarify the research gap of the relationship between customer value and CE. This study supports previous research that discusses customer value as an antecedent variable for CE.
Keywords: White Ocean Strategy (WOS); Customer Engagement (CE),; functional value; emotional value; green value; social value